Forecasting stock market prices using advanced tools of machine learning - Anwar, Md. Tawhid; Rahman, Saidur (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.